2010
DOI: 10.3109/03009734.2010.500746
|View full text |Cite
|
Sign up to set email alerts
|

Nodular fasciitis of the hand in a young athlete. A case report

Abstract: Nodular fasciitis is a rapidly growing mass, with high cellularity and mitotic activity, that can be both clinically and histologically misdiagnosed as a soft tissue sarcoma. Nodular fasciitis of the hand is an extremely rare condition. We report a 17-year-old male hand-ball player with nodular fasciitis in the dominant hand. The patient presented with a rapidly growing mass in his right hand and no history of major trauma. On physical examination, a painful mass measuring 2 cm in diameter was observed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
7
0
2
Order By: Relevance
“…Only 18 cases have been reported in the English literature. 3,6,[9][10][11][12][13][14][15][16][17][18][19] A third of these patients (n=6, 33%) suffered from pain or tenderness. In NF involving the palm, such symptoms appear to be less frequent than in other locations.…”
Section: Discussionmentioning
confidence: 99%
“…Only 18 cases have been reported in the English literature. 3,6,[9][10][11][12][13][14][15][16][17][18][19] A third of these patients (n=6, 33%) suffered from pain or tenderness. In NF involving the palm, such symptoms appear to be less frequent than in other locations.…”
Section: Discussionmentioning
confidence: 99%
“…with tumour cells at the resection margin). For nodular fasciitis, some authors believe that it is not a true tumour, but a local reactive process of fibrous tissue secondary to repeated minor trauma (Hara et al, 2010); and others believe it is an inflammatory process within connective tissue that may even respond to intra-lesional corticosteroid injections (Graham et al, 1999). Furthermore, a study of gene expression of nodular fasciitis revealed up-regulation of genes encoding inflammatory cytokines (Bacac et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Das spontane Auftreten, zum Teil mit Bagatelltraumata assoziiert, das schnelle Wachstum und die oft schwierige histopathologische Diagnosestellung verleiten zu der Annahme einer malignen Neoplasie [7,8].…”
Section: Diskussionunclassified